(untitled) (Archives of Criminology, 2023)
Drawing upon the “sociology of vindictiveness” (Young 2003; 2007) and Sumner’s (1990; 1994) work on censure the authors examine the construal, responses and treatment of individuals who have committed a sexual offence against a child/children (ICSOAC). We seek to understand the dynamics and social processes of the exclusion of others and the way negative, sectional and bureaucratised discourses, policies and practices can “other” marginalised groups, for political expediency. We argue that to fully understand these responses we need to better understand the wider social dynamics and constructions which inform and shape societal perceptions in pursuit of an essentialised “good enemy”. In line with this, we go on to outline the interaction between vindictiveness and populism in the administration of justice and situate the challenges this poses for both punishment and the rehabilitation and reintegration of individuals convicted of sexual crime.